The effects of illness script method on clinical reasoning of undergraduate nursing students: A quasi-experimental study - Gede Arya Bagus Arisudhana (Universitas Airlangga, 2022)
The improvement of clinical reasoning in nursing students is a benchmark for students' abilities in carrying out nursing care. Disease script-based learning can help students recognize the information. The purpose of this study was to determine the effect of illness scripts on the clinical reasoning ability of nursing students. The research design used was a quasi-experimental approach with a non-equivalent approach with a control group. The sampling technique used consecutive techniques. The number of samples in each group is 35 respondents, data collection using Clinical Reasoning Assessment Tools. Data analysis using Wilcoxon Signed Rank test. The results of this study indicate that there is an increase in the clinical reasoning ability of nursing students in the experimental group from the average value of 40.6 to 50.3. Most of the respondents in the experimental group had clinical reasoning at the intermediate learner level. The results of the Wilcoxon test showed that the Z-count value in the experimental group was 5.092 with a p-value = <0.001. It can be concluded that there is an effect of illness scripts method on the clinical reasoning ability of nursing students.